Kajian Perlindungan Hukum terhadap Anak yang Berkonflik dengan Hukum dalam Sistem Peradilan Pidana Anak - Leni Dwi Nurmala; Yayan Hanapi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: The purpose of this research is to find out about the forms of legal protection given to children who are in conflict with the law, especially in the juvenile justice system based on Law No. 35 of 2014 and Law No. 11 of 2012 Juvenile Criminal Justice System. Research methodology: The method used in this writing is a normative juridical approach, namely a normative juridical approach, namely legal research conducted by examining library materials or secondary data as the basic material for research by conducting a search of regulations and literature literature related to the problem under study. Results: The results of this study indicate that legal protection for children in conflict with the law in the juvenile justice system must be fully implemented by law enforcement officials at each stage of the examination, namely in the form of fulfilling and guaranteeing children's rights and prioritizing the best interests of children.